Implementing Fast Content Management to Accelerate Editorial Workflows in a Digital Newsroom - Arifin, Nofri Yudi; Suri, Ghea Paulina; Atmojo, Tri Bowo; Indra, Indra; Riswandha, Muhammad Noval; Agustini, Sherly (Sinkron : jurnal dan penelitian teknik informatika, 2026)
The rapid development of digital technology has significantly transformed the mass media industry, particularly in the production and distribution of news content. Local media organizations are increasingly required to publish news rapidly to meet the expectations of digital audiences, while still maintaining journalistic accuracy and quality. Batam Pos, as one of the leading local media outlets in the Riau Islands, faces challenges related to slow editorial workflows caused by conventional content management processes. This study aims to analyze the implementation of Fast Content Management (FCM) as a technical and managerial approach to accelerate digital news publication at Batam Pos. The research adopts a descriptive qualitative method, utilizing data collection techniques including direct observation of newsroom activities, in-depth interviews with editorial and technical staff, and literature review related to Content Management Systems (CMS) in digital media. The results indicate that the implementation of FCM shows observable improvement editorial efficiency through workflow automation, integrated collaboration features, and real-time content management. The publication cycle from writing to distribution becomes shorter without compromising content accuracy due to the presence of layered verification mechanisms within the system. This study concludes that Fast Content Management is an effective strategy for enhancing digital publication performance and can serve as a practical model for other local media organizations undergoing digital transformation.